2017
DOI: 10.1111/myc.12639
|View full text |Cite
|
Sign up to set email alerts
|

Heteroresistance and fungi

Abstract: The concept of heteroresistance refers to the heterogeneous susceptibility to an antimicrobial drug in a microorganism population, meaning that some clones may be resistant and others are susceptible. This phenomenon has been widely studied in bacteria, but little attention has been given to its expression in fungi. We review the available literature on heteroresistance in fungi and invite the reader to recognise this phenomenon as a fungal mechanism to adapt to environmental stress, which may interfere both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…It consists of the ability of a subpopulation of microorganism to adapt to high concentrations of the drug, resulting in resistant homogenous populations. However, heteroresistant strains return to the initial phenotype when the stimulus with the drug is withdrawn [78].…”
Section: Resistance In Pathogenic Yeasts: a Significant Problemmentioning
confidence: 99%
“…It consists of the ability of a subpopulation of microorganism to adapt to high concentrations of the drug, resulting in resistant homogenous populations. However, heteroresistant strains return to the initial phenotype when the stimulus with the drug is withdrawn [78].…”
Section: Resistance In Pathogenic Yeasts: a Significant Problemmentioning
confidence: 99%
“…Even though an Aspergillus colony originates from one conidium with a single nucleus, heterogeneity in the physiological activities in different regions of a colony or in different hyphal compartments within a single hyphae has been repeatedly noticed [7]. This heterogeneity is also observed for a conidial population and linked to resistance to antifungal drugs [8]. Bleichroldt et al [9] identified distinct subpopulations of A. fumigatus conidia showing different patterns of heterogeneity at the cell wall level that manifest differential fitness to the antifungal caspofungin.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroresistance to antifungal drugs is a recognized yet poorly understood subpopulation phenomenon observed in pathogenic fungi under drug pressure (14). As with bacteria such as Staphylococcus aureus (15) and Mycobacterium tuberculosis (16), studies of heteroresistance in fungi have been hampered by a lack of consistency in methodology and definitions (17, 18). Heteroresistance to FLC has been detected in clinical strains of Candida glabrata, although the mechanisms and clinical impact of this remain unknown (19).…”
Section: Introductionmentioning
confidence: 99%